STRATEGI KOMUNIKASI DALAM PEMBELAJARAN BAHASA INGGRIS MAHASISWA PROGRAM STUDI MANAJEMEN BISNIS POLITEKNIK NEGERI MANADO - Vincentius Pantow; Wingston Longdong; Walangitan Melania; Selvie R.I. Mandang (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2021)
Oral communication with English as a Foreign Language often faces various problems. There are many factors that hinder a person's communicative competence, such as linguistic problems including grammatical, lexical and phonological problems.Grammatical problems relate to the formation of correct sentences, while lexical problems involve vocabulary limitations. Then the Phonological problem refers to the way to pronounce the word. To deal with these problems, various ways are done, one of which is by using a communication strategy. This study aims to: 1). Identifying and classifying communication strategies used by students of the Manado State Polytechnic Business Management Study Program, 2) Analyzing the communication process and communication strategies in learning English. The methodology used is a qualitative descriptive approach. The data collection method is using note-taking techniques, with the basic technique of taping and elicitation. Taping is done through attentive listening, getting involved, and conversing. Elicitation techniques are performed by face-to-face. Furthermore, the recording technique is then recorded. Meanwhile, the data analysis method goes through the following stages: 1). Data selection, 2). Data reduction, 3). Presentation of data, and 4). Draw conclusions and verification. Temporary observations obtained that students use two communication strategies, namely, verbalcommunication strategies and non-verbal communication strategies.